TEKNIK PENGAMBILAN GAMBAR BERBASIS TRACKING SHOT DALAM PRODUKSI VIDEO COMPANY PROFILE PT BOOGIE APPAREL INDONESIA - Ivani Valerine Silalahi; Rici Tri Harpin Pranata (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to describe the planning process and implementation of tracking shot cinematographic techniques in the production of a company profile video for PT Boogie Apparel Indonesia, using a visual narrative approach as an effective and innovative visual communication strategy for building the company's brand identity among a wider audience. Method: This study employed a qualitative descriptive method with an audiovisual production approach, conducted through three main stages: pre-production, encompassing concept development and storyboarding; production, involving the direct application of tracking shot techniques in the field; and post-production, which included the editing and visual color grading processes. Results: The tracking shot technique was successfully applied across ten primary scenes covering operational activities, the manufacturing process, employee interactions, and a closing scene featuring the company's tagline, resulting in visual content that was dynamic, immersive, and representative of the company's identity. Novelty: This study demonstrates that a systematically planned tracking shot technique is proven effective as a visual communication strategy in company profile video production, particularly for companies operating in the manufacturing industry. This camera-movement-based cinematographic approach represents a notable innovation in digital promotional media that has not been widely examined in previous research.